Gambaran Pemeriksaan Fungsi Hati pada Pasien Sirosis Hepatis yang Dirawat di Rumah Sakit Umum Daerah Arifin Achmad Provinsi Riau Periode 2013 - 2015 - Shabrina Maharani; Dasril Efendi; Lucyana Ani Tampubolon (Fakultas Kedokteran Universitas Riau, 2018)
Diagnosis of hepatic cirrhosis enforcement requires the anamnesis, physical examination, and examination of supporting. The purpose of this research is to know the description of examination of liver function. The results showed on the basis of age age category is the most 25-65 of the year a number of 188 men (89.1%), most of which is gender male category a number of 135 people (63.98%), bilirubin total showed an increase of more than 1.1 mg/dL number of 154 people (90.59%), albumin showed a decrease of less than 3.8 g/dL number of 181 people (92.34%), AST shows an increase of more than 45 u/L number of 162 people (77.14%) ALT, shows an increase of more than 35 u/L number of 146 people (69.52%), HbsAg is present on a number of 58 patients, and 1 patient is present on the HVC.